Combining ability of grain sorghum lines selected for aluminum tolerance - Cicero Beserra Menezes; Geraldo Afonso de Carvalho Júnior; Lidianne Assis Silva; Karine Costa Bernardino; Vander Fillipe Souza; Flávio Dessaune Tardin; Robert Eugene Schaffert (Crop Breeding and Applied Biotechnology, 2014)
The purpose of this study was to estimate combining ability of 58 sorghum lines previously selected for Aluminum (Al) tolerance. One hundred sixty-five hybrids were evaluated at three levels of Al saturation (0%, 20% and 50%) at the same season. General Combining Ability (GCA) effects were significant for female lines for all three traits. GCA effects for male lines were significant only for plant height. Specific Combining Ability (SCA) effects were significant only for flowering time. The ratio GCA to SCA was greater than the unity, indicating the prevalence of additive effects for the control of Al tolerance. F7, F14, F17, F20, F21, F24, F29, F31, F41, F42, F48, F51, F54 and F55 lines contributed to increase yield, while F29, F48 and F51 also contributed to reduce flowering time. M2 was the best male line since it contributed to increase yield and plant height, and to reduce flowering time.